Effects of chicken bone powder mixed with limestone and cement on the clayey soil geotechnical characteristics - Salih Asmaa (Magazine of Civil Engineering)
Soil stabilization is aiming to enhance the geotechnical properties of soils. Traditionally, it has relied on conventional materials, such as cement and lime. However, the growing awareness of environmental sustainability has prompted researchers to explore alternatives, including waste. The employment of waste helps reduce waste deposited in landfills and decrease greenhouse gas emissions. The literature revealed that adding wastes to clay significantly improves clay’s mechanical characteristics. This study has identified alternative methods of trash disposal that would be economically and environmentally beneficial. The effect of chicken bone powder with limestone and cement on clay has been investigated. Liquid limit and plasticity index have decreased, and unconfined compressive strength of samples treated with 10%CBP+5%LS and 10%CBP+5%C up to 28 days have been increased by 2.69-fold and 4.82-fold, respectively. A reduction in the soil’s cohesion from 37.079 to 35.115 kPa and an increment in the internal frictional angle from 0.66° to 2.10° has been discovered for the mix of 10%CBP+5%LS. Compression and swell index reductions were observed with the addition of 10%CBP+5%LS and 10%CBP+5%C. From scanning electron microscopy, the binder materials caused the samples to indicate a dense and compact matrix and reduced the porosity.